Tafsir Al Bayaan - T.M. Hasbi Ash-Shiddieqy (Al Ma'arif, 1974)
Oen, Jil. II=c.1; Jil. III=c.1-3;Jil. IV= c. 1-3/ ir, jil.3,c.4-5/tr, jil.4=c.4; jil.3=c.6;jil.4=c.5/en, jil.2=.c.2/en, jil.1=c.1/stc13,jil.2,c.3